Biological activities of monoclonal antibodies to Mycoplasma pneumoniae membrane glycolipids. - Chandler, D K (1989)
A purified preparation of membranes was obtained by using a unique method of treating Mycoplasma pneumoniae with the ATPase inhibitor, diethylstilbestrol. This method was shown to yield highly purified membranes with little or no cytoplasmic contamination. These membranes were used to immunize mice for subsequent productions of monoclonal antibodies (MAbs). Hybridoma culture supernatants were screened by enzyme-linked immunosorbent assay with whole-cell M. pneumoniae and lipid extract antigens. Four stable MAbs were obtained and characterized. MAb CP3-46F5 reacted with a protein of a molecular weight of approximately 52,000 as determined by Western blot (immunoblot). MAbs CP3-50C2, CP3-53C5, and CP3-53C8 did not react with any antigens on Western blots but did bind to at least 10 distinct glycolipid bands as determined by orcinol staining on thin-layer chromatograms of M. pneumoniae lipid extracts. The MAbs did not react with similarly prepared lipid extracts from Mycoplasma genitalium, Mycoplasma neurolyticum, and Mycoplasma gallisepticum. These MAbs did not inhibit M. pneumoniae metabolism or attachment to WiDr cell cultures. The anti-glycolipid MAbs recognize determinants specific to M. pneumoniae, unlike polyclonal hyperimmune sera against M. pneumoniae, which cross-react with lipid extracts of M. genitalium.